Batch and semi-continuous fermentation with Parageobacillus thermoglucosidasius DSM 6285 for H2 production - Magda S. Ardila; Habibu Aliyu; Pieter de Maayer; Anke Neumann (Biotechnology for Biofuels and Bioproducts)
Abstract Background Parageobacillus thermoglucosidasius is a facultatively anaerobic thermophile that is able to produce hydrogen (H2) gas from the oxidation of carbon monoxide through the water–gas shift reaction when grown under anaerobic conditions. The water–gas shift (WGS) reaction is driven by a carbon monoxide dehydrogenase–hydrogenase enzyme complex. Previous experiments exploring hydrogenogenesis with P. thermoglucosidasius have relied on batch fermentations comprising defined media compositions and gas atmospheres. This study evaluated the effects of a semi-continuous feeding strategy on hydrogenogenesis. Results A batch and two semi-continuous fermentations, with feeding of the latter fresh media (with glucose) in either 24 h or 48 h intervals were undertaken and H2 production, carbon monoxide dehydrogenase (CODH) activity, and metabolite consumption/production were monitored throughout. Maximum H2 production rates (HPR) of 0.14 and 0.3 mmol min−1, were observed for the batch and the semi-continuous fermentations, respectively. Daily feeding attained stable H2 production for 7 days, while feeding every 48 h resulted in high variations in H2 production. CODH enzyme activity correlated with H2 production, with a maximum of 1651 U mL−1 on day 14 with the 48 h feeding strategy, while CODH activity remained relatively constant throughout the fermentation process with the 24 h feeding strategy. Conclusions The results emphasize the significance of a semi-continuous glucose-containing feed for attaining stable hydrogen production with P. thermoglucosidasius. The semi-continuous fermentations achieved a 46% higher HPR than the batch fermentation. The higher HPRs achieved with both semi-continuous fermentations imply that this approach could enhance the biohydrogen platform. However, optimizing the feeding interval is pivotal to ensuring stable hydrogen production.